Acetylcholinesterase assay for cerebrospinal fluid using bupivacaine to inhibit butyrylcholinesterase - Kluge, Wolfram H (BioMed Central, 2001)
BACKGROUND: Most test systems for acetylcholinesterase activity (E.C.3.1.1.7.) are using toxic inhibitors (BW284c51 and iso-OMPA) to distinguish the enzyme from butyrylcholinesterase (E.C.3.1.1.8.) which occurs simultaneously in the cerebrospinal fluid. Applying Ellman's colorimetric method, we were looking for a non-toxic inhibitor to restrain butyrylcholinesterase activity. Based on results of previous in vitro studies bupivacaine emerged to be a suitable inhibitor. RESULTS: Pharmacokinetic investigations with purified cholinesterases have shown maximum inhibition of butyrylcholinesterase activity and minimal interference with acetylcholinesterase activity at bupivacaine final concentrations between 0.1 and 0.5 mmol/l. Based on detailed analysis of pharmacokinetic data we developed three equations representing enzyme inhibition at bupivacaine concentrations of 0.1, 0.2 and 0.5 mmol/l. These equations allow us to calculate the acetylcholinesterase activity in solutions containing both cholinesterases utilizing the extinction differences measured spectrophotometrically in samples with and without bupivacaine. The accuracy of the bupivacaine-inhibition test could be confirmed by investigations on solutions of both purified cholinesterases and on samples of human cerebrospinal fluid. If butyrylcholinesterase activity has to be assessed simultaneously an independent test using butyrylthiocholine iodide as substrate (final concentration 5 mmol/l) has to be conducted. CONCLUSIONS: The bupivacaine-inhibition test is a reliable method using spectrophotometrical techniques to measure acetylcholinesterase activity in cerebrospinal fluid. It avoids the use of toxic inhibitors for differentiation of acetylcholinesterase from butyrylcholinesterase in fluids containing both enzymes. Our investigations suggest that bupivacaine concentrations of 0.1, 0.2 or 0.5 mmol/l can be applied with the same effect using 1 mmol/l acetylthiocholine iodide as substrate.